Handmade Microstrip Leaky-Wave Antenna in UHF band for Educational Purposes. - Campo-Valera, María; Poveda-García, Miguel; García-Fernández, Joaquín; Cañete-Rebenaque, David; Gómez-Tornero, José Luis (My University, 2022)
The design, manufacture and testing of a micro strip leaky-wave antenna in the UHF band is reported. The antenna is fabricated using low-cost materials and handmade techniques. This activity is intended for educational purposes and hands-on training of antenna engineering and related applications. Particularly, the proposed antenna can be used for localization of passive RFID tags and DVB-T base stations.
Keywords: Antenas - Diseño y construcción; Leaky-wave antennas; Microstrip atennas; Education; Direction finding; UHF